2021
DOI: 10.1038/s41598-021-91697-z
|View full text |Cite
|
Sign up to set email alerts
|

Large scale self-assembly of plasmonic nanoparticles on deformed graphene templates

Abstract: Hierarchical heterostructures of two-dimensional (2D) nanomaterials are versatile platforms for nanoscale optoelectronics. Further coupling of these 2D materials with plasmonic nanostructures, especially in non-close-packed morphologies, imparts new metastructural properties such as increased photosensitivity as well as spectral selectivity and range. However, the integration of plasmonic nanoparticles with 2D materials has largely been limited to lithographic patterning and/or undefined deposition of metallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…10f). 464,476 Then, NPs dipor spin-coated on the film were guided by the wrinkles and assembled into NP chains. 191,[470][471][472][473][474][475] By adjusting the geometries of the cross section and its size-match with NPs, NP chains with a controlled number of layers, width and orientation could be obtained.…”
Section: Template-directed Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…10f). 464,476 Then, NPs dipor spin-coated on the film were guided by the wrinkles and assembled into NP chains. 191,[470][471][472][473][474][475] By adjusting the geometries of the cross section and its size-match with NPs, NP chains with a controlled number of layers, width and orientation could be obtained.…”
Section: Template-directed Assemblymentioning
confidence: 99%
“…10f), have also been integrated into wrinkle templates to endow 1D NP chains and 2D chain arrays with additional optoelectronic properties. 464 Beside nanochannels and wrinkles, porous AAO is also widely used as a confining template, because its pore diameter and length can be uniformly controlled by simple manufacturing and template-removing procedures. SiO 2 and hollow carbon sphere chains, 477 Ag NP chains and Ag/Bi bimetallic nanowires, 446 and PS-b-PDMS peapods 445 have been produced within porous AAO by depositing NPs or their precursors, and sequentially removing solvent and AAO templates.…”
Section: Template-directed Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to flat substrates such as wafer or glass, metal-graphene hybrid SERS substrates have been developed with polymers for three-dimensional (3D) structuring [ 69 , 72 , 77 ] and flexibility [ 78 80 ]. Leem et al reported mechanically self-assembled AuNPs on 3D structured graphene/polystyrene (PS) substrates [ 72 ].…”
Section: Plasmonic Effect Of Graphene-based Hybrid Materialsmentioning
confidence: 99%
“…This phenomenon is caused by longitudinal coupling of dipoles between AuNSs, and is extended as particles are confined in long columns on the graphene surface. 91 Plasmonic enhancement is especially useful in electronic and sensing applications and use of surface ligands has been explored as another method to control NP assembly off templates. 92 For example, Van Lehn and co-workers model the self-assembly of 5 nm AuNSs and demonstrate that thiol-coated AuNSs in particular may aggregate due to interactions between hydrophobic ligands (Fig.…”
Section: Deterministic Assembly Of Nanoparticles Into ''Polymers'' An...mentioning
confidence: 99%